Komodifikasi Limbah Sabut Kelapa sebagai Upaya Pengembangan Produk Kreatif Berbasis Potensi Lokal dalam Mendukung Perekonomian Anggota Kelompok Tani Diporejo Desa Kedayunan - Rusti, Nanda; Widakdo, Danang Sudarso Widya Prakoso Joyo; Halil, Halil (Universitas Nusantara PGRI Kediri, 2025)
One of the sub-districts that produces the most coconuts in Banyuwangi Regency is Kabat Sub-district with an average of 7,829 tons per year. One of the villages that produces the most coconuts in Kabat Sub-district is Kedayunan Village with a harvest area of ​​426 ha and a production of 679.9 tons in 2020. However, coconut fiber waste has not been utilized optimally. Coconut fiber is a by-product and the largest part of the coconut fruit, which is around 35% of the weight of the coconut fruit. Although coconut fiber is classified as organic waste, if left untreated it will have an impact on the environment such as waste accumulation. The availability of waste that is very large in the Diporejo Farmers Group, further processing is needed so that coconut fiber waste becomes a product with high selling value and can help increase the income of farmer group members. One way to overcome this problem is by processing coconut fruit derivative products from coconut fiber into cocopeat. Cocopeat is a planting medium made from coconut fiber which has several advantages. These advantages include, as an environmentally friendly organic planting medium and has a fairly high water absorption capacity, the most important of which is being able to reduce coconut waste in the surrounding environment. In addition to coconut fiber processing activities, members of the farmer group are taught training on how to market cocopeat in the market.